Toward greater legitimacy: Online accountability practices of Ukrainian nonprofits - Asya Cooley (Administrative Sciences, 2024)
This exploratory study examined recent innovations in online accountability practices adopted by Ukrainian nonprofits. A quantitative content analysis of Ukrainian nonprofit websites evaluated their adoption of online accountability practices across five dimensions: accessibility, engagement, performance, governance, and mission. The results reveal wide variability in accountability scores and low average disclosure of performance and governance practices. Nonprofits without a listed location have lower scores. International NGOs demonstrate stronger governance than domestic groups. Associations are leaders in online innovations. Overall, Ukrainian nonprofits are not fully capitalizing on digital platforms to enhance transparency and stakeholder engagement. This study provides unique insights into online accountability among Ukrainian nonprofits and highlights opportunities for nonprofits to leverage websites as strategic management tools for greater accountability, legitimacy, and impact.
Keywords: 350; nonprofit management; nonprofit sector; online accountability; Ukraine